Rancang Bangun Sistem Informasi Geografis Pelanggan Unit Jasa Pengelolaan Sampah pada BUMDesa Catu Krewo Sedana - Widiartha, Komang; Sandika, I Kadek Budi; Kumala Dewi, Desak Putu Diah (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
Badan Usaha Milik Desa (BUMDesa) Catu Kwero Sedana is BUMDesa located in Pecatu village, South Kuta District, Badung-Bali Regency. The waste handling mechanism carried out by the waste management service unit at the BUMDesa Catu Kwero Sedana is the collection of garbage to residents' houses or businesses in the village of Pecatu. BUMDesa focuses on the quality of services provided to its customers. Until now there are still complaints from customers, especially new customers and prospective customers, related to the start of service and / or registration as new customers. The problem that often occurs is the difficulty of finding the location of garbage collection at the customer's site. If the customer registers himself through a contribution collector who is collecting customer bills, the employee in charge of transporting waste is sometimes constrained to find the customer's location. In addition, related to the amount of tariffs that will be charged to customers. Employees of garbage transport who do not know the size of the contribution rates of customers will find it difficult to provide the range of tariffs that will be charged to customers according to the rules stated in the regulations of Pecatu village. To overcome these problems, it is necessary to have a system that can provide information to employees of garbage transport regarding the position / location of garbage collection of each customer, the amount of tariff in accordance with applicable regulations, and recapitulation of payment of customer contributions. This information system can be developed based on websites with a geographic information system (GIS) model by utilizing the Application Programming Interface (API) maps owned by Google. The application of GIS to waste management has been extensively investigated and shows positive results